Management of radiation-related caries in head and neck cancer patients: Scientific evidence (Research, Society and Development, 2021)
Patients diagnosed with malignant neoplasms in the head and neck region are often treated by radiotherapy. Despite the efficiency in eradicating cancer cells, ionizing radiation can reach healthy tissues close to the tumor, causing undesirable effects to the patient, such as hyposalivation, dry mouth, mucositis, soft and hard tissue necrosis and radiation-related caries (RRC). RRC is a multifactorial and highly destructive disease, which compromises the patient’s oral function. The management of patients with RRC is becoming increasingly common in dental practice, since the cure rates for malignant neoplasms have been higher with the advances in current medicine. In this context, the present study aims to discuss the main factors related to the development of RRC, as well as the difficulties and limitations found in its treatment and control. A narrative and qualitative literature review was carried out, based on a survey of scientific articles found in the Google Scholar, Pubmed and SciELO databases, with no restriction on the year of publication and language. For this, the following keywords were used: Dental Caries; Dentin; Dental Enamel; Mouth Neoplasms; Radiotherapy. It is concluded that there is no well-defined protocol for the treatment of RRC in the literature, and the restorative process is quite challenging for dentists. It emphasizes the need for better methodology details of the study carried out and more studies on the subject in order to establish an effective clinical protocol for these patients, seeking, above all, to restore health and improve quality of life.